The Relationship Patterns of Itenas Open Spaces as the Keystones for Regenerative Design - Dwi Kustianingrum; Widji Indahing Tyas; Eka Virdianti (Indonesian Journal of Built Environmental and Sustainability, 2019)
ABSTRACT : Public open spaces designs determine the patterns of natural balance. In order to preserve its sustainability, regenerative design should be applied. As the main step of its application, an investigation of relationship patterns or keystones of the designs needs to be conducted. Using a qualitative approach, this study aims to investigate those patterns in public open spaces in Itenas compared to six other campuses in Bandung and Jakarta. The research method of analysis is descriptive.. It is concluded that the relationship patterns found in the public open spaces of the campus generally are: (1). Connectivity is formed from vehicle circulation patterns and accessibility; (2). Criteria for outdoor space that are generally desirable. While the findings specifically are (1). The relationship patterns found in Itenas relate to the response of activities, locations, times and categories of the public spaces; (2). Stimuli in the form of other activity-creating aspects; (3). In the communal and commercial facilities categories, users mix, interact; (4). There is a place of illegal stimuli causing the circulation function changes into a facility. The findings support the theories and serve as important information implementing the regenerative design in Itenas.Keywords : Relationship Patterns (Keystone), Public Open Space, Campus, Itenas, Regenerative Design